2021
DOI: 10.1007/s11631-021-00484-0
|View full text |Cite
|
Sign up to set email alerts
|

Is bicarbonate directly used as substrate to participate in photosynthetic oxygen evolution

Abstract: If the photosynthetic organisms assimilated only CO2 in the Archean atmosphere, hydroxide ion in the Archean seawater would not increase. If plants would not consume bicarbonate as a direct substrate during photosynthesis, it is difficult to explain the evolution of Earth's environment. To date, it is generally accepted that photosynthetic O2 evolution of plants come from water photolysis. However, it should be debated by evaluating the effect of bicarbonate in photosynthetic O2 evolution, analyzing the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 72 publications
0
10
1
Order By: Relevance
“…We would like to point out that the accurate Gibbs free energy calculations we report here are much higher than the misplaced earlier values reported in literature [14,70], which give 103.8 and 156.1 kJ/mol respectively for reactions ( 14) and ( 15), for the same ½O 2 stoichiometry. The difference is also seen in relative terms (for bicarbonate versus water); our calculations showing a difference of $36 kJ/mol compared to Dismukes' differential of $52.3 kJ/mol.…”
Section: Murburn 1e/2e Equilibriums With Bicarbonate As Electron Donorcontrasting
confidence: 58%
See 1 more Smart Citation
“…We would like to point out that the accurate Gibbs free energy calculations we report here are much higher than the misplaced earlier values reported in literature [14,70], which give 103.8 and 156.1 kJ/mol respectively for reactions ( 14) and ( 15), for the same ½O 2 stoichiometry. The difference is also seen in relative terms (for bicarbonate versus water); our calculations showing a difference of $36 kJ/mol compared to Dismukes' differential of $52.3 kJ/mol.…”
Section: Murburn 1e/2e Equilibriums With Bicarbonate As Electron Donorcontrasting
confidence: 58%
“…In later times, as some researchers emphatically claimed that there was no evidence for the direct roles of bicarbonate [9][10][11][12], the general opinion shifted against the "PS II-binding based effects" school of thought. In response, while a few of the original advocates toned down their support for bicarbonate being crucial [13], a few others have campaigned steadfastly for bicarbonate to play more direct roles [14][15][16]. In the context of the conundrum prevailing on bicarbonate (as well as several other additive molecules'/ions' ability to impact the photosynthetic process), we apply the murburn model of photosynthesis [17][18][19][20][21][22][23][24][25] to clarify upon several other associated facts from the literature and reason out the structure-function correlations of proteins and dynamics of molecular interactions in milieu.…”
Section: Introduction To the Additive (Bicarbonate) Sponsored Effectsmentioning
confidence: 99%
“…Diversified modes of bicarbonate use are determined by the stoichiometric relationships among protons, electrons, and inorganic carbon. Proton and bicarbonate are the substrates of photosynthetic oxygen evolution (Wu 2021). Therefore, direct bicarbonate uptake including via anion exchanger and transporters, bicarbonate dehydration via external CA and P-type H ?…”
Section: Differential Contribution Of Various Bicarbonate Use Pathwaysmentioning
confidence: 99%
“…So far, it has not been found the bicarbonate can transport across the thylakoid membranes into the thylakoid lumen (Wang et al 2011). However, bicarbonate photolysis in thylakoid membranes provides protons, electrons, and carbon dioxide, which would concentrate and elevate the CO 2 concentration at the site of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) (Wu 2021). Therefore, even if there is no direct bicarbonate use dependent on CCMs in plasma membrane, the carbon dioxide from the atmosphere continuously enters the cell membrane due to great concentration difference, which resulted from the indirect removal of inorganic carbon within the plasma membrane via bicarbonate photolysis in thylakoid.…”
Section: Capital Contribution Of Ccms In Thylakoid Membranesmentioning
confidence: 99%
“…Moreover, bicarbonate photolysis and water photolysis could both be sources of photosynthetic oxygen [8,9]. This has resulted in a revised formula of photosynthetic oxygen evolution as follows: 2H 2 O + CO 2 → H 2 O + H + + HCO 3 − → O 2 + 4e − + 4H + + CO 2 [10], which should be sourced from both bicarbonate and water in a 1:1 (mol/mol) stoichiometric relationship [11]. Hence, it confirmed that bicarbonate significantly contributes to plant growth in karst habitats.…”
Section: Introductionmentioning
confidence: 99%